Dielectric and impedance spectroscopy analysis of lead-free (1-x)(K0.44Na0.52Li0.04)(Nb0.86Ta0.10Sb0.04)O3-xBaTiO3 ceramics. Issue 10 (July 2019) - Liu, Yang; Du, Yi; Cheng, Chuanbing; Sun, Xiao; Jiang, Nan; Wang, Jiajia; Sun, Xinyue
Abstract: (1- x )(K0.44 Na0.52 Li0.04 )(Nb0.86 Ta0.10 Sb0.04 )O3 - x BaTiO3 (labeled as (1- x )KNLNTS- x BT, x  = 0.00, 0.02, 0.04, 0.06, 0.08, 0.10) lead-free ceramics were prepared by a solid-state sintering method. As the BT content increased, the phase of ceramics changed from orthorhombic (0.00 ≤ x ≤ 0.02) to orthorhombic-tetragonal (0.02 < x < 0.06) structure, and finally turned into tetragonal (0.06 ≤ x ≤ 0.10) structure. The Curie-Weiss law and modified Curie-Weiss law were applied to analyzing dielectric properties. With the increase of BT content, the relaxation degree increased, which indicated that the ceramics shown a excellent relaxation behavior. For 0.9 KNLNTS- 0. 1BT ceramics, the dispersion coefficient γ reached the maximum of 1.73, which is hugely attractive for lead-free relaxor ferroelectrics. From its variation of impedance spectroscopy with temperature, it was found that the relaxation and conduction behavior were associated with the thermal activation, and the oxygen vacancies were the potential ionic carriers. Moreover, through Arrhenius fitting, the activation energy of 0.9 KNLNTS- 0. 1BT ceramic was 0.82(6) eV, indicating that the oxygen vacancy concentration for the ceramics was high.